Critical role of tedizolid in the treatment of acute bacterial skin and skin structure infections - Ferrández O; Urbina O; Grau S (Dove Medical Press, 2016)
Olivia Ferrández,1,2 Olatz Urbina,1 Santiago Grau1,3 1Hospital Pharmacy, Hospital Universitari del Mar, Barcelona, Spain; 2Nursing Department, Universitat Pompeu Fabra, Barcelona, Spain; 3Medicine Department, Universitat Autònoma de Barcelona, Barcelona, Spain Abstract: Tedizolid phosphate has high activity against the Gram-positive microorganisms mainly involved in acute bacterial skin and skin structure infections, such as strains of Staphylococcus aureus (including methicillin-resistant S. aureus strains and methicillin-sensitive S. aureus strains), Streptococcus pyogenes, Streptococcus agalactiae, the Streptococcus anginosus group, and Enterococcus faecalis, including those with some mechanism of resistance limiting the use of linezolid. The area under the curve for time 0–24 hours/minimum inhibitory concentration (MIC) pharmacodynamic ratio has shown the best correlation with the efficacy of tedizolid, versus the time above MIC ratio and the maximum drug concentration/minimum inhibitory concentration ratio. Administration of this antibiotic for 6 days has shown its noninferiority versus administration of linezolid for 10 days in patients with skin and skin structure infections enrolled in two Phase III studies (ESTABLISH-1 and ESTABLISH-2). Tedizolid’s more favorable safety profile and dosage regimen, which allow once-daily administration, versus linezolid, position it as a good therapeutic alternative. However, whether or not the greater economic cost associated with this antibiotic is offset by its shorter treatment duration and possibility of oral administration in routine clinical practice has yet to be clarified. Keywords: tedizolid, tedizolid phosphate, acute bacterial skin and skin structure infections, oxazolidinone, linezolid resistance